Lung cancer cells and their sensitivity/resistance to cisplatin chemotherapy: Role of microRNAs and upstream mediators - Ashrafizadeh, Milad; Zarrabi, Ali; Hushmandi, Kiavash; Hashemi, Farid; Moghadam, Ebrahim Rahmani; Owrang, Marzieh; Hashemi, Fardin; Makvandi, Pooyan; Goharrizi, Mohammad Ali Sheikh Beig; Najafi, Masoud; Khan, Haroon (Cellular signalling, 2021)
Cisplatin (CP) is a well-known chemotherapeutic agent with excellent clinical effects. The anti-tumor activity of CP has been demonstrated in different cancers such as breast, cervical, reproductive, lung, brain, and prostate cancers. However, resistance of cancer cells to CP chemotherapy has led to its failure in eradication of cancer cells, and subsequent death of patients with cancer. Fortunately, much effort has been put to identify molecular pathways and mechanisms involved in CP resistance/sensitivity. It seems that microRNAs (miRs) are promising candidates in mediating CP resistance/sensitivity, since they participate in different biological aspects of cells such as proliferation, migration, angiogenesis, and differentiation. In this review, we focus on miRs and their regulation in CP chemotherapy of lung cancer, as the most malignant tumor worldwide. Oncogenic miRs trigger CP resistance in lung cancer cells via targeting various pathways such as Wnt/β-catenin, Rab6, CASP2, PTEN, and Apaf-1. In contrast, onco-suppressor miRs inhibit oncogene pathways such as STAT3 to suppress CP resistance. These topics are discussed to determine the role of miRs in CP resistance/sensitivity. We also describe the upstream modulators of miRs such as lncRNAs, circRNAs, NF-κB, SOX2 and TRIM65 and their association with CP resistance/sensitivity in lung cancer cells. Finally, the effect of anti-tumor plant-derived natural compounds on miR expression during CP sensitivity of lung cancer cells is discussed. [Display omitted] •Cisplatin is widely applied in cancer chemotherapy with promising clinical outcomes,•Resistance of cancer cells to chemotherapy has restricted its therapeutic potential,•MicroRNAs (miRs) are potent regulators of cellular events,•MiRs induce/inhibit cisplatin resistance in lung cancer cells,•Upstream mediators such as long non-coding RNAs, circular RNAs and NF-κB regulate miRs in resistance/sensitivity of lung cancer cells to cisplatin chemotherapy.